PEMBAGIAN NILAI TAMBAH PETANI PLASMA PIR-SUS KELAPA SAWIT - Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2005)
The aims of this study are to analyze the farmer’s value added, efficiency and the factors affecting the value added distribution. Location of the research is taken by using purposive sampling method on NES [Nucleus Estate and Smallholders] at the regency of Muara Enim in South Sumatera Province. A sample of Farmer’s selected using stratified random sampling. The qualitative descriptive analysis is also applied in of this study through measuring intermediate cost variables, efficiency and value added distributions. The result of this research showed that farmer’s low of the value added and efficiency performance. Efficient Farmer’s is reached when value added and productivity high, lower cost production, and labor exploitation. Factors inefficiency causing lost of the production surplus, by factors interest rate exploited, and increase disguised unemployment. The height Farmer’s quality and efficiency are to increase the equality for value added distributions. The more rigid on value added distributions influenced by inefficiency, lowest education, and medium productivity ages. All the impacted assumedly exploitation mechanism to impact of decrease farmer’s efficient and increase to gap value added distribution, and it does to affecting on the poverty. Keywords: cost, efficiency, farmer’s quality, exploitation, value added distributions